Aprendizagens profissionais da docência nos anos iniciais do ensino fundamental no contexto das avaliações em larga escala de matemática - Almeida, Aila Stefania de [UNESP] (2015)
The SARESP system was established in 1996, scoping to evaluate the quality of teaching and learning, sponsor educational strategies and support for the planning and implementation of teaching strategies as well as education policies. The objective of this study was to investigate if: i) the teacher's planned contact with video records and textual classes taught by him, as well as models of interpretation of possible functional relationships between the actions of students and teaching practices arranged by the teacher and ii) establising correspondences between the actions of students and learning arranged in MRA, could favor apprendiceships of teaching defined by the identification, by the teacher, of possible relations of functional dependence between features of the students and teaching practices and evaluation willing by the teacher. A professor of 5º year of elementary school attended a packet municipal school. The procedure was divided into two phases. In Step I, after performing an interview with the teacher about the planned didactic unities, the lessons' recording procedure took place. Starting on the lessons registries, the teacher had to identify learning skills shown by the students, those learning rates and the teaching conditions on which they occurred. Beforehand the teacher's report transcription and the episodes description, relationg teacher's actions and the students' reponse and subsequent teacher's actions, the teacher estimated correspondence between the learning skills expected in SARESP's MRA and the shown learning skills. In Step 2, the methodological procedures used in Step 1 were refuted. The obtained results showed that the learning skills were nominated in different terminology from the MRA and missing identification of possible stimulus relations control. After showing the participant the used procedure, there was a decrease in the number of those directions which was not possible to find link to the...